Islamic Rural Bank Employee Performance: Role of Motivation, Compensation, and Work Environment - Hizbul Khootimah Az-zaakiyyah; Farid Hidayat; Abu Muna Almaududi Ausat; Suherlan Suherlan (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2022)
Rural banks in Indonesia have been experiencing a significant growth. Each company has diverse workforce. Excellent employees will contribute significantly to achieve the company's goals. However, some companies disregard any factors that can lead to optimal employee performance. The purpose of this study was to determine the effect of motivation, compensation, and work environment on the employee performance. This was a case study conducted at PT. BPRS Madina Mandiri Sejahtera Yogyakarta. A quantitative technique based on variance Structural Equation Modeling (SEM) and Partial Least Square (PLS) was used to acquire a better understanding of the relationship between variables. Questionnaires were used to collect 28 responses from the company’s employees. The finding revealed that compensation was a deterrent for companies that have not received awards in the previous five years. As a result, the company’s management must pay more attention to work compensation related to more efficient and effective use of human resources. The higher the employees’ salary, the more achievements achieved by the employees. The higher the number of high-performing employees, the lower the cost of non-essential work.